Belongingness to Canada: Synthesizing Canadianness and Muslimness among Newly Emergent Canadian Muslims - Muhammad Izzul Haq (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
The recent statistic reveals the number of Canadian Muslims increases multifold in decades. It is predicted that the Canadian Muslim population will grow significantly. The demographic postures of varied Canadian Muslims offer several features requiring scholarly attention and action from all interested stakeholders to look into the situation. That is to evoke Canadianness among those newly emergent Canadian Muslims who came to Canada as immigrants or born here and grown-up as Muslim. When each boundary is negotiated, the spectrum of Muslimness and Canadian-ness is synthesized in the making. This ongoing situation demands particular action to nurture a sense of belongingness for newly emergent Canadian Muslims to protect and promote Canadian multicultural society amidst external and internal challenges such as Islamophobia and radicalism. Based on scoping reviews on selected pieces of literature, the idea of finding a new model or denomination of Islam in Canada is a convincing step to synthesize Canadianness and Muslimness, which reflect the empirical situation of newly emergent Muslims in Canada. The history of the first mosque built in Canada taught us how the synthesis can be practically applied, how flexible Islam can be genuinely promoted, and the lines of doctrine and cultural difference can be deliberately blurred. This ethos demonstrates compatibility with Canadian values of openness and respect for diversity.